IMBALANCES IN THE INDIAN ECONOMY - N. V. Galistcheva (Vestnik MGIMO-Universiteta)
The main task of this research is the analysis of the key imbalances in the Indian economy, as well as their reasons and consequences. The article highlights the main directions of the Indian government’s policy in the 1990–2000s aiming to overcome these imbalances. The author focuses on the imbalances in the financial, real and external economic sectors of the Indian economy and underlines features of using labour, financial, scientific and technical resources, which are necessary for its successful development. The article underlines contradictory conditions of the present economic development in India and coexistence of the capitalist and pre-capitalistic ways of production (the small-scale industry), including the cottage industries, in the Indian real sector. At the same time the contemporary economic policy of the Indian government doesn’t aim at the elimination of the pre-capitalistic way of production but at the large-scale business’ activity restrictions in the sphere of the small-scale industry. This policy aims at the creation of favorable economic conditions for the small-scale industry. The author notes the main problems of the social sector of the Indian economy and in the human resources development and points out in the sphere of education the unresolved problems connected with equality of educational opportunities and availability of secondary and higher education for the considerable strata of the Indian population and also with deterioration of academic standards etc. The article also presents statistical data on the present state of the Indian external debt, fiscal deficit, the foreign exchange reserves as well as the dynamics of the Indian external trade, foreign direct investments’ inflow and remittances of the Indian diasporas.